IEEE SENSORS 2014 Proceedings 2014
DOI: 10.1109/icsens.2014.6985189
|View full text |Cite
|
Sign up to set email alerts
|

Detection of 2,4-dinitrotoluene (DNT) using gravure printed surface enhancement Raman spectroscopy (SERS) flexible substrate

Abstract: In this work, gravure printing was used to fabricate a thin film of silver (Ag) nanoparticle ink on flexible polyethylene terephthalate (PET) sheet as an efficient surface enhanced Raman spectroscopy (SERS) substrate. The printed SERS substrate was used for the detection of an explosive organic compound: 2,4-dinitrotoluene (DNT), in vapor phase. An enhancement factor of four, in the intensity of the Raman spectrum of DNT vapor, was observed when compared to target molecules absorbed on bare PET. An increase in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…19,20 For instance, Emamian et al fabricated a substrate consisting on AgNPs 'ink' on a sheet of polyethylene terephthalate for detection of DNT from the vapour phase. 21 Another study by Tamane et al demonstrated vapour phase detection of nitro-explosives by using AgNPs on Si where they enclosed the substrate in a sealed tube with explosive simulant at thermodynamic equilibrium. 22 They concluded that desorption and decomposition of TNT in the vapour phase hindered detection by SERS, as they observed SERS enhancement after 10 seconds followed by a decreasing signal intensity over time with splitting of several key Raman bands.…”
Section: Introductionmentioning
confidence: 99%
“…19,20 For instance, Emamian et al fabricated a substrate consisting on AgNPs 'ink' on a sheet of polyethylene terephthalate for detection of DNT from the vapour phase. 21 Another study by Tamane et al demonstrated vapour phase detection of nitro-explosives by using AgNPs on Si where they enclosed the substrate in a sealed tube with explosive simulant at thermodynamic equilibrium. 22 They concluded that desorption and decomposition of TNT in the vapour phase hindered detection by SERS, as they observed SERS enhancement after 10 seconds followed by a decreasing signal intensity over time with splitting of several key Raman bands.…”
Section: Introductionmentioning
confidence: 99%
“…For explosives detection using SERS technique, great number of substrates have been fabricated, provided a various enhancement factors. These substrates include noble metal, semi-conductors and hybrids of metallic-semiconductor substrates [18][19][20][21][22]. However, most of the high efficient enhancement for explosives among all were obtained on metallic substrates that is due to the poor vapor pressure of explosives compared to other probe such us dyes, thus explosive molecules require strong mechanism to enhance their Raman signals, and that can be achieved by electromagnetic mechanism which can be mainly obtained by using nobel-metal substrates such as gold or silver [23,24].…”
Section: Introductionmentioning
confidence: 99%